Purification of dye industries wastewater via crystallization: effect of operation time and solution concentration: article - Mohd Zolfakar, Mohd Nizamuddin; Ab Hamid, Farah Hanim (2018)
The high capacity of water consumption also results in high amount of wastewater produced and released to ecosystem and will affect the ecology. Purification of dye wastewater using crystallization, specifically freeze concentration technique provides more width to any process plants towards waste management. It is essential to introduce a new method of freeze concentration to overcome the weaknesses of conventional method, and therefore to enhance the wastewater purification development for a better quality of water treatment.